Translating Culture: Reading the Paratexts to Aimé Césaire’s Cahier d’un retour au pays natal - Watts, Richard (TTR, 2000)
AbstractTranslating Culture: Reading the Paratexts to Aimé Césaire's Cahier d'un retour au pays natal — This article is concerned not with the linguistic translation of a Caribbean text, but with its cultural translation. It presents the argument that the paratexts to the multiple editions of Aimé Césaire's Cahier d'un retour au pays natal fonction principally as instruments of cultural translation. It also describes how the transfigurations of the Cahier's paratext over time and across cultures serve as markers for the changing epistemes of "Caribbean culture" and "Francophone Caribbean Literature."